(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The basic concept of marketing is to match the supply and demand in a macroeconomic scale while sales are the concept to match the need, utility and solution in the micro economic scale. The barter system was the ancient mode of trading in which the producers exchange the products with each other according to their need in a common place and it was the first mode of marketing noticed by Herodotus, the ancient Historian and the earliest statement about the origin of marketing activity was made by Herodotus only (Dixon & Donald, 1967). The Indians only introduced the gold and silver coinage system and started adopting the same in retail trade. The terminology of ‘marketing’ was emerged to represent ‘buying and selling’ in ‘Turkey’ (old Asia Minor) and then it spread to other regions like Greek and whole over the world. The marketing concept was later transformed from ‘detrimental individual gain to social bonding’ and the ‘consumer behaviourism’ was observed in consumption and based on this the trading pattern also started changing. The thoughts of great philosophers like Socratic Philosophers, Plato, St Augustin of Hippo, st Thomas Aquinas, had explained the social behaviour towards balancing demand and supply, social behaviour, self-management of excess and scarce supplies by self-balancing pricing system (Jons & Shaw, 2002). Now the present market is a composition of traditional marketing system and digital marketing system. There are three categories of customers; traditional buyers, online buyers, and hybrid buyers who use both.Modern marketing is a replica of the old system and main difference is in the exchange of goods and services. In the real world promotion and transaction occurs through virtual platform and the information and computational system replace traditional marketing activity. The central philosophy of online is the virtual reality in tangibility instead of sensing real product, information transfer is factual than emotional, system based than humane, self-decision than peer or family influence, virtual monetary transaction than real hard currency, convenience than exertion, quick than delayed and so on